The role of insulin receptor substrate (IRS) proteins in oncogenic transformation - Gorgisen, G.; Gulacar, I. M.; Ozes, O. N. (Cellular and Molecular Biology, 2017)
Insulin Receptor Substrate (IRS) proteins are the main cytoplasmic adaptor molecules involved in transducing extracellular signals from receptors to downstream proteins. This protein family have pivotal roles on maintenance, distribution and regulation of signaling networks. Since IRS1/2 interact with and transmits signals from the receptors of insulin, Insulin Like Growth Factor 1 (IGF1), prolactin, growth hormone (GH), leptin, Vascular Endothelial Growth Factor (VEGF), TrkB, ALK and integrins this promoted scientist to think that IRS1 may have functions in cell proliferation, tumorigenesis and metastasis. Therefore, over the past decade, studies on IRS proteins and their functions in cancer has been increased and these studies provided valuable results claiming the involvement of IRS1/2 in cancer development. In this review, we discuss the function and contributions of IRS1 and IRS2 in development of breast cancer.